Linagliptin Inhibits Lipopolysaccharide-Induced Inflammation Concentration-Dependently And -Independently - Sato N (Dove Medical Press, 2019)
Naoki Sato,1,2 Yuya Nakamura,1,3 Shiho Yamadera,4 Masahiro Inagaki,1,5 Sachiyo Kenmotsu,5 Hiroshi Saito,4,6 Tatsunori Oguchi,1 Mayumi Tsuji,1 Hirokazu Chokki,1 Isao Ohsawa,3 Hiromichi Gotoh,3 Shinichi Iwai,6 Yuji Kiuchi1 1Department of Pharmacology, Showa University School of Medicine, Shinagawa-ku, Tokyo, Japan; 2Department of Research Center, Tanabe Pharmacy Inc., Tokyo, Japan; 3Department of Nephrology, Saiyu Soka Hospital, Soka City, Saitama-ken, Japan; 4Department of Hospital Pharmaceutics, Showa University School of Pharmacy, Shinagawa-ku, Tokyo, Japan; 5Fuculty of Arts and Sciences at Fujiyoshida, Showa University, Fujiyoshida City, Yamanashi-ken, Japan; 6Department of Healthcare and Regulatory Sciences, Showa University School of Pharmacy, Shinagawa-ku, Tokyo, JapanCorrespondence: Yuya NakamuraDepartment of Pharmacology, Showa University School of Medicine, 1-5-8 Hatanodai, Shinagawa-ku, Tokyo, JapanTel +81-3-3784-8125Fax +81-3-3787-4790Email y.nakamura@med.showa-u.ac.jpPurpose: Dipeptidyl peptidase-4 inhibitors, including linagliptin, prevent inflammation. However, the in vitro effects of linagliptin are unclear. Moreover, although linagliptin inhibits lipopolysaccharide (LPS)-induced inflammation, the anti-inflammatory effects of linagliptin in this context are not concentration-dependent. In the absence of LPS-binding protein (LBP), the pro-inflammatory effects of LPS involve pathways other than the Toll-like receptor (TLR) 4 pathway. Here, we aimed to determine the anti-inflammatory mechanisms of linagliptin in an experimental model in which LBP was added to the medium.Methods: Human U937 monocytes were cultured at 1 × 106 cells/mL in Roswell Park Memorial Institute medium and differentiated into macrophages using phorbol myristate acetate. All processes were carried out in medium containing 10% fetal bovine serum (FBS). After 48 hrs of culture, we replaced the medium and pretreated the cells with 100, 250, 500, or 2500 nM linagliptin for 1 hr. We exchanged the medium again, and the cells were treated with 1 ng/mL LPS with or without 100, 250, 500, or 2500 nM linagliptin. Interleukin (IL)-6 and LBP in the supernatant, nuclear factor (NF)-κB/p65 in the nucleus, and reactive oxygen species (ROS) in the cells, as important markers of the mechanism of inflammation induction by LPS, were measured using enzyme-linked immunosorbent assay kits.Results: Linagliptin significantly prevented LPS-stimulated IL-6 production and intranuclear NF-κB/p65 levels in a concentration-dependent manner. LPS-induced intracellular ROS levels were significantly decreased by linagliptin at all concentrations. LBP levels were markedly higher in FBS-containing medium than in medium without FBS. However, LBP levels did not change following administration of linagliptin and/or LPS.Conclusion: Concentration-dependent and -independent inflammatory suppression was observed following linagliptin treatment in the context of LPS-induced pro-inflammatory responses. Thus, our findings suggested that linagliptin induced two different mechanisms to repress inflammation, i.e., TLR4-dependent and -independent mechanisms.Keywords: linagliptin, lipopolysaccharide-binding protein, interleukin-6, intranuclear subunit of nuclear factor-κB/p65, reactive oxygen species